Assessment of the force-velocity relationship during vertical jumps: influence of the starting position, analysis procedures and number of loads - Janicijevic, D.; Knezevic, O. M.; Mirkov, D. M.; Pérez-Castilla, A.; Petrovic, M.; Samozino, P.; Garcia-Ramos, A. (European Journal of Sport Science, 2020)
This study aimed to compare the reliability and magnitude of the force-velocity (F-V) relationship parameters between the squat jumps performed from the 90° (SJ90) and self-preferred knee angle (SJpref). A secondary aim was to explore the effect of the analysis procedure (force platform [FP] and Samozino's [SAM] method) and the number of loads tested (three- and two-point methods) on the F-V relationships. Twelve men were tested in two sessions during the SJ90 and SJpref. Two identical blocks of jumps were performed in each session against three external loads. The F-V relationship parameters (maximum force, maximum velocity, F-V slope and maximum power) were determined at each block through the FP and SAM procedures using the data collected under three (three-point method) or only the two most distant loads (two-point method). The average coefficient of variation (CV) of the four F-V parameters revealed a higher reliability for the SJ90 compared to the SJpref (5.86% vs. 7.55%; CVratio = 1.29) with more pronounced differences using the FP (CVratio = 1.43) than the SAM procedure (CVratio = 1.14), and higher reliability for the SAM compared to the FP (6.14% vs. 7.27%; CVratio = 1.18). The SJpref and SAM procedures provided comparable or higher magnitude of the F-V relationship parameters than the SJ90 and FP, respectively. The three- and two-point methods revealed a comparable reliability and trivial differences in the magnitude of the F-V relationship parameters. The routine testing procedure of the F-V relationship could be simplified using the SJpref, the SAM procedure and the two-point method.